2022
DOI: 10.3389/fcimb.2021.790243
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum-Shaping Atlastin Proteins Facilitate KSHV Replication

Abstract: Kaposi’s sarcoma-associated herpesvirus (KSHV) has two life cycle modes: the latent and lytic phases. The endoplasmic reticulum (ER) is the site for KSHV production. Furthermore, ER stress can trigger reactivation of KSHV. Little is known about the nature of the ER factors that regulate KSHV replication. Atlastin proteins (ATLs which include ATL1, ATL2, and ATL3) are large dynamin-related GTPases that control the structure and the dynamics of the ER membrane. Here, we show that ATLs can regulate KSHV lytic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Recent studies have reported the interactions between viral infection and host cellular ER-shaping proteins such as ATL3, RTN3, and Lunapark, which are involved in ER network formation [167]. ER-shaping atlastin proteins (ATL1, -2, and -3), which induce ER membrane fusion, are recruited to the Zika virus (ZIKV) replication site and co-localized with the viral proteins, facilitating ZIKV replication [168]. ATL3s can also regulate Kaposi's sarcoma-associated herpesvirus (KSHV) lytic activation and infection [169].…”
Section: Virus and Modification Of Endoplasmic Reticulummentioning
confidence: 99%
“…Recent studies have reported the interactions between viral infection and host cellular ER-shaping proteins such as ATL3, RTN3, and Lunapark, which are involved in ER network formation [167]. ER-shaping atlastin proteins (ATL1, -2, and -3), which induce ER membrane fusion, are recruited to the Zika virus (ZIKV) replication site and co-localized with the viral proteins, facilitating ZIKV replication [168]. ATL3s can also regulate Kaposi's sarcoma-associated herpesvirus (KSHV) lytic activation and infection [169].…”
Section: Virus and Modification Of Endoplasmic Reticulummentioning
confidence: 99%